Queue city: Authority and trust in the waiting line. Issue 100 (March 2019) - Wiesel, Ilan; Freestone, Robert
Abstract: Queuing is central to the way city dwellers spend their time, access critical resources and perform social differences. In this paper, we explore the tactics of individuals negotiating access to goods, speed and status in the waiting line; and the strategies of authorities managing these queues. We propose that across numerous queues throughout the city, the interaction of such tactics and strategies produces a dynamic set of social relations and emotions that become prominent features of the urban experience: trust, rage, competition, boredom, relaxation, hostility, and anxiety among others. Drawing on ethnographic observations in Sydney, we examine the relationship between processes of commodification, authoritarianism and self-choreography in queue dynamics. Focusing specifically on airport terminal and bus waiting lines, we examine the ways commodification and authoritative queue management cultivate disciplined subordination, but also resistance. In more self-organized queues, social relations of trust and cooperation between strangers – critical components of a functional city – continue to be acculturated. However, we emphasise the need for an urban geography of queues that moves beyond the micro-dynamics of waiting lines in isolation, and makes visible larger scale processes of commodification and authoritarianism, affecting even the most spontaneous of queues.